Enforcement of foreign judicial acts under German law - Akimbekova, S.A. (Bulletin of the Karaganda University “Law Series”, 2019)
The article is devoted to an urgent and significant problem of the modern international civil process – recognition and enforcement of foreign court decisions. The inclusion of our country in the world economic and legal space makes it necessary to ensure the free circulation of not only goods, services, money and people, but also judicial acts that resolved conflicts between participants in international civilian traffic. Considerable attention is paid in the article to the common law doctrine, the achievements of which, despite the difference in legal systems, can be used to create an effective mechanism for the recognition and enforcement in Kazakhstan of acts of foreign courts. The article is devoted to the study of the characteristics of the enforcement of foreign judicial acts under German law. At present, one can hardly doubt the urgency of the problem of the mutual enforcement of court decisions. The question of the execution of a foreign decision is essentially the question of extending its legal force to the internal legal space of another state, about giving it the same legal properties of legal force and general obligation that are inherent in national decisions.